Time and distance in acceleration of road commercial vehicles - Navarro, Hélio A. [UNESP]; Canale, Antonio Carlos; D'Elboux, José Eduardo; Saraiva, José Roberto; Valtas, Nicolas Basile (SAE International, 1997)
The time and the distance traveled during the acceleration and the velocity retaking are parameters used for the comparison and the project of vehicles. In this paper equations for the calculation of those parameters are presented. Several criteria are presented for the shift gears. It is also verified the occurrence or not of total slip during the acceleration of the vehicle. The theoretical models were implemented in a developed computational system. Such system was applied in a Mercedes-Benz do Brazil sample vehicle, in order to facilitate comparisons between the simulate values and the experimental road tests. Copyright © 1997 Society of Automotive Engineers, Inc.
Keywords: Computational system; Mercedes Benz; Road tests; Theoretical models; Automobiles; Roads and streets